Co-Occurrence of Pheochromocytoma-Paraganglioma and Cyanotic Congenital Heart Disease: A Case Report and Literature Review - Zhao, Bingbin; Zhou, Yi; Zhao, Yi; Zhao, Yumo; Wu, Xingcheng; Bi, Yalan; Luo, Yufeng; Ji, Zhigang; Rong, Shi (Frontiers in Endocrinology, 2018)
Pheochromocytoma-paraganglioma (PHEO-PGL) and cyanotic congenital heart disease (CCHD) are both rare diseases. We reported a 30-year-old patient with a right adrenal gland nodule and a retroperitoneal mass and history of functional single atrium and ventricle. 123I-metaiodobenzylguanidine scintigraphy showed intense uptake in both lesions. Laboratory investigation demonstrated elevated urinary norepinephrine. Preoperative α-blockade was initiated. A successful open resection of right adrenal and retroperitoneal masses was performed. Pathological examination confirmed PHEO-PGL. Postoperative urinary norepinephrine returned to normal level. A systematic case review in English publications in PubMed and EMBASE suggested a hypothesis that there may exist a possible link between PHEO-PGL and hypoxia from CCHD, which was also indicated in our case. Due to higher risk for PHEO-PGL, a lower threshold of suspicion should be considered in CCHD patients. Therefore, active screening and early treatment of PHEO-PGL are recommended in CCHD patients and clinicians should keep on a long-term follow-up to monitor PHEO-PGL recurrence if hypoxia is not corrected.